Tied Free-Field boundaries to enhance numerical accuracy of earthquake simulations - González Acosta, J. León; Van den Eijnden, Abraham P.; Hicks, Michael A. (Frontiers in Built Environment, 2025)
Free-Field (FF) boundaries have previously been developed to replicate the (infinite) far-free-field domain in the simulation of earthquake loading problems. Although they can yield accurate results under certain conditions, it has been observed that significant problems can occur if the behaviour of the material near the boundaries is highly non-linear or incorporates cyclic attributes, or if the boundaries are located close to the domain of interest. To address the inaccuracies caused by the use of traditional FF boundaries, a novel technique is proposed: Tied Free-Fields. This technique combines the principles of both standard earthquake boundary conditions (that is, Tied-Degree (TD) and FF boundaries) to accommodate earthquake loading at the domain boundaries in a direct and economical fashion. The proposed solution has been tested using one and two-dimensional benchmarks and an advanced constitutive model. The results show a significant improvement in accuracy over traditional FF boundaries in the modelling of surface settlements and computed energy released, as well as a significant improvement in computational efficiency over TD boundaries in the modelling of asymmetric problem domains.